2009
DOI: 10.1603/029.102.0128
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Palmitate, an Acaricidal Compound Occurring in Green Walnut Husks

Abstract: Walnut, Juglans regia L., is known for its insecticidal activities to a range of herbivores and microbes. Isolation and identification of bioactive compounds from walnut is a potential approach for the development of new pesticides. Laboratory experiments were carried out to investigate the acaricidal activities of green husk extracts of walnut. Bioassay-guided fractionation of petroleum-ether extracts of walnut led to the identification of a common plant-borne fatty acid ester, methyl palmitate (MP), which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Moreover, it was identified in the green walnut husks producing strong acaricidal activity. [75] As reported by Jordan et al, [76] we found that ketones are less abundant in the profile of fruit volatiles and are more abundant in leaves. In many cases, the flavor and aroma of many fruits is due to the presence of volatile ketones, potentially derived from carotenoids.…”
Section: Headspace Leaf Volatilessupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, it was identified in the green walnut husks producing strong acaricidal activity. [75] As reported by Jordan et al, [76] we found that ketones are less abundant in the profile of fruit volatiles and are more abundant in leaves. In many cases, the flavor and aroma of many fruits is due to the presence of volatile ketones, potentially derived from carotenoids.…”
Section: Headspace Leaf Volatilessupporting
confidence: 76%
“…demonstrated the effectiveness of methyl hexadecanoate in combating inflammation in several experimental models. Moreover, it was identified in the green walnut husks producing strong acaricidal activity …”
Section: Resultsmentioning
confidence: 99%
“…Among these, the insecticidal activity of farnesol has also been reported [58]. Methyl palmitate and myristic acid also possess insecticidal properties [59, 60]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the LC 50 of the ninth fraction was 1.26 g/l after 24 h in slide-dip assays , and this value was higher than the values obtained for b-sitosterol-3-O-heptadeca-8Z,11Zdienoate. In addition, Wang et al (2009) showed that within 24 h of exposure to a glass slide treated with methyl palmitate isolated from green husk extracts of walnut (Juglans regia L.), adults of T. cinnabarinus exhibited significant mortality (97.9%) at a concentration of 10.00 g/l, whereas much lower concentrations of b-sitosterol-3-O-heptadeca-8Z, 11Z-dienoate (4.00 g/l) were required to cause a similarly dramatic effect. However, to the best of our knowledge, the active compound LLX-1 (b-sitosterol-3-O-heptadeca-8Z, 11Z-dienoate) is a novel compound and isolated from S. nigrum for the first time.…”
Section: Discussionmentioning
confidence: 99%